FRI0558 PREGNANCY OUTCOMES IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS – A FIRST JOINT ANALYSIS OF A EUROPEAN COLLABORATION OF PREGNANCY REGISTERS. (2nd June 2020) - Meißner, Y.; Costedoat-Chalumeau, N.; Förger, F.; Goll, D.; Moltó, A.; Özdemir, R.; Wallenius, M.; Strangfeld, A.; Fischer-Betz, R.
Abstract : Background: Axial spondyloarthritis (axSpA) can affect women in their childbearing age. But data on pregnancy in axSpA patients are mainly retrospective and highly heterogeneous [1]. Objectives: The aim of this analysis was to investigate pregnancy outcomes and health of live born children in women with axSpA in four prospective cohort studies. Methods: Data of European pregnancy registries that collaborate in the European Network of Pregnancy Registries in Rheumatology (EuNeP) were analysed: EGR2 (France), RePreg (Switzerland), RevNatus (Norway) and Rhekiss (Germany). Eligible women had a diagnosis of axSpA and a pregnancy outcome reported until June-September 2019. Data were analysed descriptively by every registry and provided to the coordinating centre. Results: A total of 328 pregnancies in 288 women were investigated. Mean age of patients ranged from 31 to 33 years. Disease duration (3-8 years) and proportion of patients with a positive HLA-B27 (64-74%) varied (Table 1 ). The axSpA diagnosis was either classified by ASAS criteria (fulfilment in EGR2: 93%, RePreg: 65%, RevNatus: 86%) or by ASAS criteria for axial/ peripheral SpA (Rhekiss: 81/ 34%). Rates for preterm birth were ≤5%, and congenital malformations were reported in 4 out of 287 neonates (Table 2 ). Conclusion: Differences in study design and classification criteria result in slightly different patient populations in each registry. The outcome of pregnancies was favourable. Preterm birth rates are within rates reported by the WHO for the EU general population. However, a selection bias of rather planned and well-controlled pregnancies cannot be ruled out. This is the first collaborative analysis of the EuNeP registries. Descriptive data were combined, and will be – as a next step – pooled together. Funding: This work was supported by a research grant from FOREUM Foundation for Research in Rheumatology. References: [1] Giovannopoulou E et al. Curr Rheumatol Rev. 2017;13(3):162-9. Disclosure of Interests: Yvette Meißner Speakers bureau: Pfizer, Nathalie Costedoat-Chalumeau Grant/research support from: UCB to my institution, Frauke Förger Grant/research support from: Unrestricted grant from UCB, Consultant of: UCB, GSK, Roche, Speakers bureau: UCB, GSK, Doreen Goll: None declared, Anna Moltó Grant/research support from: Pfizer, UCB, Consultant of: Abbvie, BMS, MSD, Novartis, Pfizer, UCB, Rebecca Özdemir: None declared, Marianne Wallenius: None declared, Anja Strangfeld Speakers bureau: AbbVie, BMS, Pfizer, Roche, Sanofi-Aventis, Rebecca Fischer-Betz Consultant of: UCB, Speakers bureau: Abbvie, Amgen, Biogen, BMS, Celgene, Chugai, GSK, Janssen, Lilly, Medac, MSD, Novartis, Roche, UCB, Pfizer.